2001
DOI: 10.1039/b103883b
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants and Arrhenius parameters for the reactions of OH radicals and Cl atoms with CF3CH2OCHF2, CF3CHClOCHF2 and CF3CH2OCClF2, using the discharge-flow/resonance fluorescence method

Abstract: Rate constants have been determined for the reactions of OH radicals and Cl atoms with the three partially halogenated methyl-ethyl ethers, CF 3 CH 2 OCHF 2 , CF 3 CHClOCHF 2 and CF 3 CH 2 OCClF 2 , using discharge-flow techniques to generate the OH radicals and the Cl atoms and resonance fluorescence to observe changes in their relative concentrations in the presence of added ether. For each combination of radical and ether, experiments were carried out at three temperatures between 292 and 410 K, yielding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
7
19
0
Order By: Relevance
“…As shown in Fig. 7, a similar correlation exists for HFEs [1][2][3][4][5][6][7]9,10,13,20,30,31]. Linear least-squares analysis of the data in Fig.…”
Section: Implications For Atmospheric Chemistry Estimation Of the Reasupporting
confidence: 65%
“…As shown in Fig. 7, a similar correlation exists for HFEs [1][2][3][4][5][6][7]9,10,13,20,30,31]. Linear least-squares analysis of the data in Fig.…”
Section: Implications For Atmospheric Chemistry Estimation Of the Reasupporting
confidence: 65%
“…For the reaction CF 3 CH 2 OCHF 2 with OH (R1) or Cl (R2), two H‐abstraction channels are feasible. Three experimental studies were reported for reaction R1 by Zhang et al,4 Beach et al,5 and Oyaro et al6 in the temperature range of 292–402 K, and the measured rate constants show good agreement. The kinetics of reaction R2 has attracted considerable attention experimentally.…”
Section: Introductionmentioning
confidence: 62%
“…The individual CVT/SCT rate constants of each reaction channel ( k 1a , k 1b , k 2a , k 2b and k 5a , k 5b , k 5c , k 5c′ ), the total rate constant k 1 , k 2 , k 5 , and the available experimental values5–11 are plotted in Figure 4, the temperature dependence of the k 1a / k 1 , k 1b / k 1 , k 2a / k 2 , k 2b / k 2 and k 5a / k 5 , k 5b / k 5 , k 5c / k 5 . k 5c′ / k 5 branching ratios are plotted in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to investigate the reaction mechanism of halogen with HFEs. The reactivity of OH/Cl with HFEs has been theoretical and experimental studied in the past literatures,[1–8] and few rate constants data are available for the Cl atom reactions of CF 3 CH 2 OCH 3 ,[1] CH 3 CH 2 OCF 3 ,[1] CF 3 CH 2 OCHF 2 ,[2–4] CF 3 CH 2 OCClF 2 ,[4] and CF 3 CHFOCF 3 ,[5] the corresponding rate values at 298 K are (1.8 ± 0.9) × 10 −11 , (2.2 ± 0.8) × 10 −12 , (3.1 ± 0.1) × 10 −14 , (3.2 ± 0.2) × 10 −15 , and (3.1 ± 2.5) × 10 −14 cm 3 molecule −1 s −1 , respectively. The theoretical investigation of the reaction halogen with CF 3 CH 2 OCF 3 is desirable to give a further understanding of the mechanism of this multiple channel reaction and to evaluate the rate constant.…”
Section: Introductionmentioning
confidence: 99%